A Socialization Program to Enhance Community Knowledge of Islamic and Conventional Economics in Rajawana Village, Karangmoncol District, Purbalingga Regency - Mahmudah, Anis (Society : Jurnal Pengabdian Masyarakat, 2025)
This community service program was conducted in Rajawana Village, Karangmoncol District, Purbalingga Regency, with the aim of improving public understanding of Islamic and conventional economics. The activity was motivated by the rapid growth of Islamic banking and financial institutions in Indonesia, which has not been matched by adequate public literacy, especially in rural areas where communities still predominantly rely on conventional systems. The program was implemented on August 1, 2025, using a lecture method combined with interactive discussions and question-and-answer sessions. The materials were presented in three subtopics: (1) the definition of economics, Islamic economics, and conventional economics; (2) the characteristics of both systems; and (3) the key differences between them. The results showed a 35% increase in participants’ knowledge scores, along with greater willingness to adopt sharia-based financial practices. Farmers, traders, and small business actors demonstrated growing interest in alternatives such as murabahah, mudharabah, and musyarakah. However, the program also revealed structural challenges, including limited access to Islamic financial institutions and inadequate digital infrastructure. These findings suggest that socialization efforts must be complemented by continuous mentoring, replication of similar programs in other rural areas, and stronger collaboration with local Islamic financial institutions to ensure sustainability and long-term impact